The Algorithm of Tafsīr: Characteristics of Content and Patterns of Audience Reception in the Case of @anugerahwulandari - Rezwandi, Rezwandi (Izzatuna: Jurnal Ilmu Al-Qur'an dan Tafsir, 2025)
This study examines the characteristics of Al-Qur’an interpretation on the TikTok account @anugerahwulandari and audience reception in the digital da'wah context. A qualitative-descriptive approach is applied through the Digital Da'wah Theory and Stuart Hall's Reception Theory (encoding/decoding). Data were collected via virtual observation and documentation of videos and netizen comments, then analyzed with open-axial-selective coding to map message construction and audience meaning-making patterns. Results show that @anugerahwulandari utilizes taḥlīlī and thematic methods, referencing various classical and contemporary commentaries. This practice builds scholarly legitimacy and enhances reference validity amidst authority issues in digital spaces. At the reception level, comment analysis identifies three decoding positions: dominant-hegemonic (affirming interpretation and creator authority), negotiated (reconstructing meaning based on religious backgrounds and personal experiences), and oppositional (criticizing or rejecting narratives). These findings suggest that TikTok interpretation represents a communicative adaptation preserving validity while triggering tensions between scholarly authority, concise audiovisual formats, and evolving audience reception dynamics within contemporary digital da'wah spaces. Abstrak Penelitian ini menganalisis karakteristik tafsir Al-Qur’an pada akun TikTok @anugerahwulandari serta resepsi audiens dalam konteks dakwah digital. Pendekatan kualitatif-deskriptif digunakan melalui kerangka Teori Dakwah Digital dan Teori Resepsi Stuart Hall (encoding-decoding). Data dihimpun via observasi virtual dan dokumentasi video serta komentar netizen, lalu dianalisis memakai teknik open-axial-selective coding guna memetakan konstruksi pesan dan pola pemaknaan audiens secara komprehensif. Hasilnya penelitian menunjukkan akun @anugerahwulandari menerapkan metode tafsir taḥlīlī dan tematik dengan merujuk berbagai kitab klasik maupun kontemporer. Praktik ini bertujuan membangun legitimasi keilmuan serta meningkatkan validitas rujukan konten di tengah isu otoritas tafsir di ruang digital. Pada level resepsi, analisis komentar menunjukkan tiga posisi decoding; dominant-hegemonic (menerima tafsir secara afirmatif), negotiated (merekonstruksi makna sesuai latar religius dan pengalaman pribadi), dan oppositional (mengkritik atau menolak narasi tafsir). Temuan ini menegaskan tafsir TikTok sebagai adaptasi komunikatif yang menjaga validitas rujukan, sekaligus memicu ketegangan antara otoritas keilmuan, format audiovisual ringkas, dan dinamika resepsi audiens di ruang dakwah digital kontemporer.